BUSINESS DEVELOPMENT: INNOVATIVE STRATEGIES AND DIGITAL TRANSFORMATION - PALIANYTSIA, Vladislav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The development of entrepreneurship is a key factor in economic growth and innovative development in the modern world. One of the most important components of the company’s success is the definition of effective strategies aimed at achieving competitive advantage and sustainable development in the conditions of constant changes in the world economy. Digitization, which is the process of introducing digital technologies into all areas of business, plays an important role in the modern development of entrepreneurship. It allows enterprises to optimize management processes, increase production efficiency, improve the quality of products and services, and also ensure rapid adaptation to changes in the market. Innovative strategies and digital transformation are two key concepts that complement each other in the conditions of modern business. Innovation strategies include the development and implementation of innovative ideas, products, services or processes that allow organizations to stand out in the market and provide competitive advantages. Digital transformation, on the other hand, means transforming a business through the adoption of digital technologies and changing business models to achieve efficiency, innovation and improved customer engagement. The purpose of the work is to determine the directions of entrepreneurship development, taking into account innovative strategies and digital transformations. The main methods used in the work are: methods of analysis and synthesis to determine the main innovative strategies and directions of digital transformation for the development of entrepreneurship; methods of deduction and induction for determining directions of entrepreneurship development: comparative method, graphic method for displaying results. One of the key strategies for the development of the enterprise is the innovation strategy, which involves the active implementation of innovative ideas, technologies and approaches in all spheres of the enterprise. Innovations allow enterprises to create competitive advantages, take leading positions in the market and ensure sustainable development in the future. In this context, it is important to take into account the trends of digital transformation, which determine the strategic decisions of enterprises in the direction of using digital technologies to improve management, optimize processes and create new products and services. Digital transformation can become a mechanism for the implementation of innovative strategies, as well as contribute to their successful implementation. For example, the use of data analytics, artificial intelligence and other digital tools can help identify new opportunities for innovation and the development of new products or services. Digital technologies can also support rapid innovation by improving processes, reducing development time and implementing new solutions. Successful digital transformation requires a clear strategy that takes into account the organization’s business goals, customer needs and competitive environment. In addition, it requires an internal change of culture and processes in the company to ensure the successful implementation of digital initiatives. Therefore, innovative strategies and digital transformation interact to create competitive advantages and ensure the success of modern businesses. Therefore, the development of entrepreneurship in the conditions of the modern world is impossible without the implementation of effective strategies aimed at innovation and digital transformation. These strategies allow enterprises not only to survive in the competitive environment, but also to successfully develop and occupy leading positions in the market in the future.